BLOCKCHAIN TECHNOLOGY USAGE ON INTELLECTUAL PROPERTY RIGHTS (TSUL LEGAL REPORT, 2026)
This research searches for the potential opportunities of blockchain technology in transforming intellectual property (IP) protection aspects on law and its implications for sustainable development goals, particularly those related to peace, justice, and strong institutions. By providing a transparent and immutable ledger for tracking IP ownership, blockchain offers a secure platform to combat fraud and misrepresentation in IP transactions. Additionally, smart contracts can automate IP enforcement, further enhancing protection measures and reducing human intervention. Beyond IP protection, blockchain fosters transparency in copyright ownership and transactions, facilitating fair compensation for creators and discouraging piracy through secure and traceable transactions. However, challenges such as accessibility, regulatory hurdles, and technological adoption remain significant barriers. Despite these limitations, integrating blockchain in IP protection offers transformative opportunities to establish more equitable systems, enhance trust, and streamline processes across various industries. Collaboration between stakeholders and standardized frameworks is essential for maximizing blockchain’s potential in IP protection and advancing sustainable development goals. This alignment can lead to more robust and transparent institutional frameworks.